Matrix Transformations and Disk of Convergence in Interpolation Processes - Chikkanna R. Selvaraj; Suguna Selvaraj (International Journal of Mathematics and Mathematical Sciences)
Let 𝐴𝜌 denote the set of functions analytic in |𝑧|<𝜌 but not on |𝑧|=𝜌(1<𝜌<∞). Walsh proved that the difference of the Lagrange polynomial interpolant of 𝑓(𝑧)∈𝐴𝜌 and the partial sum of the Taylor polynomial of 𝑓 converges to zero on a larger set than the domain of definition of 𝑓. In 1980, Cavaretta et al. have studied the extension of Lagrange interpolation, Hermite interpolation, and Hermite-Birkhoff interpolation processes in a similar manner. In this paper, we apply a certain matrix transformation on the sequences of operators given in the above-mentioned interpolation processes to prove the convergence in larger disks.